Structure and thermoelectric properties of bismuth telluride—Carbon composites. (March 2018) - Trawiński, Bartosz; Bochentyn, Beata; Gostkowska, Natalia; Łapiński, Marcin; Miruszewski, Tadeusz; Kusz, Bogusław
Graphical abstract: Highlights: Carbon nanotubes and amorphous carbon were introduced into bismuth telluride matrix. Carbon additives led to an increase of a phonon part of thermal conductivity. Carbon additives led to a decrease of an electric conductivity and Seebeck coeff. Abstract: Carbon nanotubes and amorphous carbon have been introduced into a bismuth telluride matrix (0.15 and 0.30 wt.% ratio) to investigate the influence of the carbon on the composite's thermoelectric properties. Composites with well-dispersed additives have been obtained by sonication and ball-milling methodology. Carbon nanotubes and an amorphous carbon addition led to a decrease in electric conductivity from 1120 S/cm to 77 S/cm. The absolute value of the Seebeck coefficient was found to be reduced, changing from −113 μV/K +2 μV/K, this is attributed to electron trapping by an amorphous carbon. For all investigated composites the phonon contribution of the thermal conductivity increased in comparison with a specimen without carbon additives.